A Identity Theft: A Modern “Gateway” Crime - Ilieva, jana (International Scientific Journal Vision, 2017)
Each year, millions of people are becoming victim of identity theft - a modern type of crime that consists of abuse of one’s identity in order to acquire property gain. The growing trend of this type of crime has stimulated many authors to qualify it as “epidemic” or “national crisis”, asking the national jurisdictions to react with taking over of appropriate legal measures and regulations, which do not pass by the Republic of Macedonia. However, the concern and the responsibility for preserving the identity and for protection of the personal data, remains in the hands of individuals and their selfawareness and knowledge of which depends on whether and to what extent, they will be ready to protect their identity.